From forward to spot prices: Producers, retailers and loss averse consumers in electricity markets - Valeria Di Cosmo; Elisa Trujillo-Baute (Fondazione Eni Enrico Mattei (FEEM), 2018)
The benefits of smoothing demand peaks in the electricity market has been widely recognised. European countries such Spain and some of the Scandinavian countries have recently given to the consumers the possibility to face the spot prices instead of having a fixed tariffs determined by retailers. This paper develops a theoretical model to study the relations between risk averse consumers, retailers and producers, both in the spot and in the forward markets when consumers are able to choose between fixed tariffs and the wholesale prices. The model is calibrated on a real market case - Spain - where since 2014 spot tariffs were introduced beside the flat tariffs for household consumers. Finally, simulations of agents behavior and markets performance, depending on consumers risk aversion and the number of producers, are used to analyse the implications from the model. Our results show that the quantities the retailers and the producers trade in the forward market are positively related with the loss aversion of consumers. The quantities bought by the retailers in the forward market are negatively related with the skewness of the spot prices. On the contrary, quantity sold forward by producers are positively related with the skewness of the spot prices (high probability of getting high prices increase the forward sale) and with the total market demand. In the spot market, the degree of loss aversion of consumers determine the quantity the retailers buy in the spot market but does not have a direct effect on the spot prices.
Keywords: D40; L11; Q41; 330; Electricity Spot Market; Electricity Forward Market; Risk Aversion